Molecular Biomarkers in Cutaneous Photodynamic Therapy: A Comprehensive Review - Jorge Naharro-Rodriguez; Stefano Bacci; Montserrat Fernandez-Guarino (Diagnostics)
Background/Objectives: Photodynamic therapy (PDT) is widely utilized in dermatology for the treatment of various skin conditions. Despite its effectiveness, the exact biomolecular changes underlying therapeutic outcomes remain only partially understood. This review, through a transversal approach, aims to provide an in-depth exploration of molecular biomarkers involved in PDT, evaluate its underlying mechanisms, and examine how these insights can contribute to enhanced treatment protocols and personalized therapy approaches. Methods: A narrative review of the literature was conducted, targeting peer-reviewed articles and clinical trials that focus on PDT and its molecular biomarker effects on dermatological conditions. The databases searched included PubMed, Scopus, and Web of Science, and the inclusion criteria encompassed original research articles, systematic reviews, and meta-analyses in English. Results: PDT effectively reduces the expression of critical biomarkers such as p53, Cyclin D1, and Ki-67 in AK and other cancerous lesions, leading to reduced cell proliferation and increased apoptosis. Additionally, PDT promotes extracellular matrix remodeling and stimulates collagen production, which has a rejuvenating effect on the skin and a promising role in the treatment of chronic wounds. Conclusions: PDT represents a powerful and versatile treatment option for various dermatological conditions due to its ability to target cellular pathways involved in proliferation and apoptosis. Further research into optimizing treatment parameters and combining PDT with other targeted therapies may enhance patient outcomes, reduce resistance, and pave the way for more individualized therapeutic approaches in dermatology.